Select the Sex of Your Next Calf Prior to Mating: Using Sexed Semen - Gary R. Hansen (EDIS)
Through recent advances in reproductive technology, scientists have the ability to pre-select the sex of mammalian offspring prior to mating. This is accomplished through a procedure known as flow cytometry cell sorting where X- (female) or Y-(male)-chromosome-bearing cells are sorted based on DNA content of the sperm cell. This document is AN163, one of a series of the Animal Sciences Department, UF/IFAS Extension. Original publication date April, 2006.